2010
DOI: 10.1007/s00296-010-1494-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic hand osteoarthritis in two ethnic groups living in the same geographic area

Abstract: The aim of the study was to compare the prevalence of radiographic hand osteoarthritis (OA) and its association with age, sex, body mass index in two ethnic groups, Russian and Buryats who reside in the same geographic area. It was a cross-sectional observational study. The study population comprised ethnic Russians (N = 572) and Buryats (N = 327) from the Barguzinsky District of the Buryat Republic, Russian Federation. OA was evaluated in 14 joints of the left hand according to Kellgren and Lawrence's grading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, the higher prevalence of other OA subtypes (knee and hip OA) in Black subjects and the descriptive methodology used in both of these studies (limiting the opportunity to adjust for the effects of other potential risk factors) made it unclear whether the reported associations were confounded by other variables. Moreover, the observation that there was similar prevalence and severity of hand OA between Russian and Buryat populations living in the same area (8) and no statistically significant difference in terms of the prevalence of symptomatic hand OA between Black and non-Black subjects in the Third National Health and Nutrition Examination Survey (9) suggests that environmental factors are most likely more important for the development of hand OA than racial differences. The aim of this comparative analysis was to reassess this question and evaluate the effects of race on radiographic and symptomatic hand OA in a US population, since the effects of other hand OA risk factors are well-balanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the higher prevalence of other OA subtypes (knee and hip OA) in Black subjects and the descriptive methodology used in both of these studies (limiting the opportunity to adjust for the effects of other potential risk factors) made it unclear whether the reported associations were confounded by other variables. Moreover, the observation that there was similar prevalence and severity of hand OA between Russian and Buryat populations living in the same area (8) and no statistically significant difference in terms of the prevalence of symptomatic hand OA between Black and non-Black subjects in the Third National Health and Nutrition Examination Survey (9) suggests that environmental factors are most likely more important for the development of hand OA than racial differences. The aim of this comparative analysis was to reassess this question and evaluate the effects of race on radiographic and symptomatic hand OA in a US population, since the effects of other hand OA risk factors are well-balanced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Black subjects experience an increased prevalence and higher severity of radiographic and symptomatic knee and hip OA, and hereditary, environmental, and biomechanical factors have been suggested as possible explanations for this difference (7). However, there is little evidence supporting a potential association between race and hand OA; no difference in the prevalence of symptomatic hand OA was found between Black and non-Black subjects in cross-sectional surveys or between Russian and Buryat populations living in the same area (8,9).…”
Section: Introductionmentioning
confidence: 99%